Strategic financial planning over the lifecycle : a conceptual approach to personal risk management - Charupat, Narat; Huang, Huaxiong; Milevsky, Moshe Arye, 1967- (Cambridge : Cambridge University Press, 2012)
This book on personal financial planning and wealth management employs the lifecycle model of financial economics. The central idea of 'consumption smoothing' is used to connect chapters and topics such as saving and investment, debt management, risk management and retirement planning. The first part of the book is nontechnical and aimed at a wide audience with no special technical background. The second part of the book provides a rigorous presentation of the lifecycle model from first principles using the calculus of variations. The accompanying website is found at http://www.yorku.ca/milevsky/?page_id=185.
Machine generated contents note: 1. Introduction and motivation; 2. Mathematical preliminaries - working with interest rates; 3. Personal balance sheet and human capital; 4. Consumption smoothing and optimal savings; 5. Debts, loans, and mortgages [Canadian content]; 6. Personal income taxes [Canadian content]; 7. Risk, utility, and insurance; 8. Mortality risk and life insurance; 9. Investment and diversification; 10. The mathematics of portfolio diversification; 11. Housing decisions; 12. Pensions and retirement [Canadian content]; 13. Advanced material*: Part I. Continuous time and the calculus of variations; 14. Advanced material*: Part II. Stochastic optimal control and the HJB equation; 15. Concluding thoughts and next steps.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Finance, Personal; Risk management; Wealth -- Management